UMPSA VC targets 6 key focus areas to remain excellent and more competitive - Mimi Rabita, Abd Wahit (UMPSA, 2025)
PEKAN, 12 March 2025 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dr. Yatimah Alias, has identified six key focus areas to develop a competitive university community by prioritising the ability to respond to technological, industrial, and global changes.